202k views
3 votes
Simplify the following expression to simplest form using only positive exponents. 5

Simplify the following expression to simplest form using only positive exponents. 5-example-1

1 Answer

2 votes

(16y^(28))/(x^(16))

Step-by-step explanation:

Exponent rule :


(a*b)^n\text{ = a}^2b^n


(32x^(-20)y^(35))^{-(4)/(5)}=\text{ 32}^{(4)/(5)}(x^(-20))^{(4)/(5)}(y^(35))^{(4)/(5)}

Since


32^{(4)/(5)}\text{ = 16}

You can replace it in the equation


16(x^(-20))^{(4)/(5)}(y^(35))^{(4)/(5)}

Since


Simplified\text{ : }(x^(-20))^{(4)/(5)}\text{ = }(1)/(x^(16))
Simplified\text{ : \lparen}y^(35))^{(4)/(5)}\text{ = }y^(28)

You can replace them in the equation


16*(1)/(x^(16))*y^(28)\text{ = }(16y^(28))/(x^(16))

User MSIslam
by
5.9k points